2010
DOI: 10.1007/s11258-010-9721-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experimental inundation and sediment deposition on the survival and growth of two herbaceous riverbank plant species

Abstract: Flow and sediment regimes of floodplain rivers around the world have been changed by river regulation and land management, altering the ecological processes structuring riparian plant communities. However, the combined effects of inundation and sedimentation processes on riparian plant survival and growth are poorly understood. The separate and interactive effects of inundation duration and sedimentation depth on survival, growth and vegetative reproduction of two herbaceous clonal river bank plant species, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…However, the complex and varied response of different aquatic and terrestrial species to alterations of the frequency and duration of floodplain inundation (Poff and Zimmerman, 2010) suggests that floodwater inundation alone does not singularly control ecological response. In some cases changes in sedimentation may be as important as changes in inundation frequency and duration in determining ecological response Lockaby et al, 2005, Walls et al, 2005Corenblit et al, 2009;Jolley et al, 2009;Lowe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the complex and varied response of different aquatic and terrestrial species to alterations of the frequency and duration of floodplain inundation (Poff and Zimmerman, 2010) suggests that floodwater inundation alone does not singularly control ecological response. In some cases changes in sedimentation may be as important as changes in inundation frequency and duration in determining ecological response Lockaby et al, 2005, Walls et al, 2005Corenblit et al, 2009;Jolley et al, 2009;Lowe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During long overwintering periods, plants are exposed to multiple environmental stresses, such as drought, flooding and ice cover (Bertrand & Castonguay 2003). In aquatic ecosystems associated with flooding, sedimentation can cause burial of aquatic plants by sand (Lowe et al 2010, Pan et al 2012. Previous studies have demonstrated that burial may change abiotic and biotic conditions such as light radiation (Brown 1997), temperature (Baldwin & Maun 1983, Zhang & Maun 1990) and activity of pathogens (van der Putten et al 1993, D'Hertefeldt & van der Putten 1998, thus modifying plant morpho logy and physiology, and affecting survival and growth (Little & Maun 1996, Maun 1998, Yu et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation in combination with inundation can impose strong limitations on plant growth and survival7, which might be attributed to more severe oxygen depletion111522. Therefore, the morphological adjustments of wetland plants to simultaneous inundation and sedimentation are thought to be more pronounced than changes that occur under only one of these conditions2.…”
mentioning
confidence: 99%